PENEGASAN DAN PERLUASAN OBJEK DAN SUBJEK SENGKETA ANTAR PESERTA DALAM PROSES PEMILIHAN UMUM - Jamil, Jamil; Siboy, Ahmad (HUKUM PEMBANGUNAN EKONOMI, 2022)
This article analyzes the dispute settlement in general elections, especially on the norms of Article 466 of Law Number 7 of 2017 concerning General Elections, which regulates the formulation of electoral process disputes which do not emphasize the object of dispute between election participants or there has been a vacuum of the norm. On the object of dispute between election participants. This research is normative legal research with a statutory and conceptual approach. The results of the study indicate that the object of the dispute between election participants and the election organizers (KPU) is a decree issued by the election administrator, who is a state administrative official. Meanwhile, the disputes between election participants are civil disputes whose object of the dispute is an unlawful act. Thus it needs to be an affirmation of the object of the dispute because disputes do not only occur between election participants and election organizers but can also occur between election participants. with people (naturlijk persoon) and legal entities